Antiplatelet and anticoagulation regimen in patients with mechanical valve undergoing PCI – State-of-the-art review. (1st August 2018) - Gajanana, Deepakraj; Rogers, Toby; Iantorno, Micaela; Buchanan, Kyle D.; Ben-Dor, Itsik; Pichard, Augusto D.; Satler, Lowell F.; Torguson, Rebecca; Okubagzi, Petros G.; Waksman, Ron
Abstract: A common clinical dilemma regarding treatment of patients with a mechanical valve is the need for concomitant antiplatelet therapy for a variety of reasons, referred to as triple therapy. Triple therapy is when a patient is prescribed aspirin, a P2Y12 antagonist, and an oral anticoagulant. Based on the totality of the available evidence, best practice in 2017 for patients with mechanical valves undergoing percutaneous coronary intervention (PCI) is unclear. Furthermore, the optimal duration of dual antiplatelet therapy after PCI is evolving. With better valve designs that are less thrombogenic, the thromboembolic risks can be reduced at a lower international normalized ratio target, thus decreasing the bleeding risk. This review will offer an in-depth survey of current guidelines, current evidence, suggested approach for PCI in this cohort, and future studies regarding mechanical valve patients undergoing PCI. Highlights: Best practice for patients with mechanical valves undergoing PCI is unclear Access of choice should be radial artery Second-generation drug-eluting stents should be the preferred stent Triple therapy with oral VKA+Clopidogrel+Aspirin should be avoided Dual therapy (oral VKA+Clopidogrel) duration should be 12 months for ACS and 1 month for elective